2007
DOI: 10.1016/j.paid.2006.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and discriminant validity of religiosity measures among church members and non-members

Abstract: Convergent and discriminant validity of religiosity measures among church members and non-members Scheepers, Peer; Janssen, Jacques; Reitsma, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This finding indicates that those with high levels of intrinsic orientation most liked settings judged to be particularly coherent and easy to grasp. Decades of research has shown that intrinsic orientation is strongly related to religious adherence, being positively associated with church attendance, prayer frequency, and the experience of God (Reitsma et al, 2007). Batson (1976) characterized intrinsic orientation as predictive of a "compulsive, conforming, and unquestioning true believer" (p. 32), which is consistent with empirical findings linking the construct to conventionalism (Kahoe, 1977) and more conservative religious beliefs (Ghorpade, Lackritz, & Moore, 2010).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding indicates that those with high levels of intrinsic orientation most liked settings judged to be particularly coherent and easy to grasp. Decades of research has shown that intrinsic orientation is strongly related to religious adherence, being positively associated with church attendance, prayer frequency, and the experience of God (Reitsma et al, 2007). Batson (1976) characterized intrinsic orientation as predictive of a "compulsive, conforming, and unquestioning true believer" (p. 32), which is consistent with empirical findings linking the construct to conventionalism (Kahoe, 1977) and more conservative religious beliefs (Ghorpade, Lackritz, & Moore, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…Following their judgments of the religious settings, participants completed scale items assessing their religious orientation (Reitsma, Scheepers, & Janssen, 2007). The three orientations were as follows: Intrinsic orientation (9 items; α = .88), Extrinsic orientation (9 items; α = .71), and Quest orientation (10 items; α = .77).…”
Section: Procedure Measures and Stimulimentioning
confidence: 99%
“…Six items were adapted from previous research (Batson et al, 1993;Reitsma, Scheepers, & Janssen, 2007) to assess intrinsic, extrinsic, and quest motivations of religiosity. Two items (e.g., "Religion is especially important to me because it answers many questions about the meaning of life") were combined to assess intrinsic motivation (α = .94).…”
Section: Religious Motivationmentioning
confidence: 99%